The Cycle of Colonial Oppression and Violence in Doris Lessing’s the Children of Violence: A Study of Martha Quest - Nazki, Sameeul Haq (MultiTech Publisher, 2024)
This paper explores the pervasive theme of colonial oppression, violence and their cyclical nature in Doris Lessing’s Martha Quest, (1952) first of the series of five novels in the Children of Violence (1969). Lessing uses her literary prowess to dissect the complexities of human behavior and societal dynamics through the lens of her protagonist, Martha Quest. This cyclical nature of colonial violence manifests not only physically but also as an insidious psychological inheritance, shaping the characters’ lives and decisions. The analysis focuses on Lessing’s portrayal of the inevitability of violence in human affairs, highlighting the continuous struggle for personal autonomy amidst external conflicts and internal turmoil. The quest for meaning in a fractured world becomes a central motif as characters seek solace and understanding in a world marred by violence and chaos. The paper highlights Lessing’s profound insights into the human condition and the persistent shadow of colonial violence in modern history. The study ultimately aims to contribute to a deeper understanding of Lessing’s work and its relevance to contemporary discussions on violence, identity, and historical memory.